Exploiting Regional Heterogeneity to Test Wage Setting Theories - Firm Size Wage Effects in Urban and Rural Regions - Johannes Ludsteck (European Regional Science Association (ERSA), 2014)
We exploit regional differences in labour market density to conduct a simple empirical test of dynamic monopoly and selection wage theories. According to selection wage theories employers offer above-average wages in order to attract more applicants. This allows them to be choosier and to select only the most productive workers. High wage offers reach more potential applicants in densely populated regions and can therefore be expected to be more important there. Observationally similar predictions arise in models of dynamic monopsony. The empirical implication, that firm-size wage effects should be more pronounced in urban labour markets, is tested empirically based on the German employment register data. Our results are in favour of monopsony and selection wage theories.
Keywords: R12; J31; 330; firm size wage effects; urban wage premium; wage differentials; selection wages; dynamic monopsony